Improving the Professionalism of Human Resources for the Indonesian National Police through Strengthening Supervision - Kurniawan, Rudy Cahya (Faculty of Law, Universitas Negeri Semarang, 2023)
Public distrust is only one example of the result of the poor performance and professionalism of the Police. The research method used by this study is an empirical research method that examines the implementation of strengthening as an effort to realize the professionalism of the Indonesian National Police in a progressive legal perspective with Socio-Legal. The data analysis method used is qualitative analysis which emphasizes more on the deductive and inductive inference processes as well as on the dynamics of the relationship between observed phenomena using scientific logic. The implementation of strengthening the supervision of the Police of the Republic of Indonesia in realizing professionalism is carried out well through their respective ranks and function units. The factors supporting and inhibiting the strengthening of the supervision of the Indonesian National Police are divided into two, namely the driving factor and the inhibiting factor. The driving factors consist of good coordination / cooperation between functional units, Itwasda's limited authority in handling public relations and community support for the existence of Itwasda. Meanwhile, the inhibiting factors consist of non-one-door mechanisms, bureaucratic errors from related functional units, the number of members of the Public Relations sub-section is less than the overall task carried out, inconvenience in handling and taking action against colleagues, people who do not understand the public relations mechanism and the complexity of the investigation process. until the decision is made.